Characterisation of the redox protein Thioredoxin from the gastric pathogen Helicobacter pylori - Fox, Áine T. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2004)
Gastric colonisation by the Gram-negative bacterium Helicobacter pylori is the primary cause of peptic ulceration, type B chronic gastritis, gastric adenocarcinoma, and is linked to the progression of gastric MALT lymphoma. H. pylori infection elicits a host immune response and this results in an oxidative burst from macrophages and polymorphonuclear leukocytes recruited to the site of infection. As a microaerophile, H. pylori is particularly susceptible to the effects of reactive oxygen metabolites. Many studies have highlighted the vital role played by sulphydryl groups (-SH) in response to oxidative stress and the thioredoxin (Trx) and glutaredoxin (Grx) systems play a major role in protecting cells from oxidative damage. H. pylori is significantly different from other prokaryotes in terms of deficiency in its complement of thiol-dependent redox active proteins. The bacterium is equipped with only one of the two major, almost ubiquitous, intracellular disulphide reducing systems, the Trx system and lacks the Grx system. Thioredoxins (Trxs) are small redox proteins present in almost all sequenced prokaryotic and eukaryotic cells which share a similar three-dimensional structure and a possess a highly conserved -CGPCcatalytic motif H. pylori possess two distinct thioredoxin proteins, one of which, Trx2 has a unique redox active site, -CPDC-. The results of this study provide further insight into the role of the redox protein Trx2 in the gastric pathogen, H. pylori.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin